COMPETENCES OF TEACHERS WHO HAVE CHANGED THEIR PROFESSION FROM CLASSROOM TEACHING TO SOCIAL STUDIES TEACHING DUE TO THE NEW EDUCATION SYSTEM OF 4 + 4 + 4 (A CASE STUDY) - Selçuk Beşir DEMİR (Fırat University, 2019)
The purpose of this study is to investigate the competencies of teachers in the field of social studies who have changed their fields of profession from classroom teaching. The study was carried out pursuant to the design of case study method that is one of the qualitative research methods. Among the purposeful sampling methods, the Critical case sampling method was used in the study. The study group of the research consists of 2 branch teacher in the city X (pseudonym). In the research, observation form and semi-structured interview form were used as a data collection tool. All the interviews and observations were recorded throughout the research. The recordings were computerized through the Microsoft Word processing program as raw data without being subjected to any screening. Each transcript in the research was analyzed by using line by line analysis analysis approach. A 95-minute interview was had within the scope of the research.Inductive descriptive analysis, content analysis and the constant comparison technique were used in the interpretation of the observation and interview data. In the light of the findings obtained in the study, it was found that the participants, who had changed their fields of profession from classroom teaching to social studies teaching, assumed that they had qualifications in terms of their field-specific self-competencies; however, they lacked the field-specific competencies identified by the Ministry of National Education and they were not aware of these deficiencies. It was concluded that the participants did not have enough knowledge and skills as to the mission and aims of the Curriculum for Social Studies Lesson and basic approaches and premises of social studies instruction. It was also found that teacher-centered behaviorist instruction was adopted in which learners are passive and abstract and purely theoretical knowledge is presented to be learned through rote-learning instead of learner-centered and activity-centered instruction in which learners are active in line with the constructivist approach